UMA PROPOSTA DE MODELO DE GESTÃO PARA AS PEQUENAS E MÉDIAS EMPRESAS (PMEs): UM ESTUDO DE CASO MÚLTIPLO DO SETOR QUÍMICO NO ESTADO DO RIO DE JANEIRO - Vieira Neto, Julio (2008)
This dissertation treats subjects regarding the Small and Medium Enterprise (SME´s) in Brazil and in the world, where it is appeared socioeconomic importance, since this the kind of organizations hires more labor force than any other. The study analyzes the difficulties in the field of the management that these enterprise face in order to keep on competitive in the market, it classification as for the size in function of the activity branch and recommendations to be more successful. It is discussed the subject of the entrepreneurship based on the cause and effect analysis among the difficulties in the administration of the business and the mortality of these organization type. Since the high interest rates collected by financial institutions make it difficult to obtain financing, the importance of venture capital is evaluated as a support to the SME´s. Several authors consider that the main responsible factor for the inhibition of the growth and break of the Small and Medium Enterprise in Brazil and in the world t is the lack of management capacity on the part of their proprietors, following for deficiency in the reception of financial resources that hinders the management of the cash flow. It is intended in this dissertation to present a proposal of a management of model based in the theory that can guide these organizations in the transport of their businesses through more balanced actions. As investment alternative it is proposed the venture capital that requested by the investor s criteria, capitalize these organizations without compensation of collection of interests. For the development of the research, the descriptive method wasadopted and as approach strategy the study of multiple cases in companies of small and medium size in the chemical section of the State of Rio de Janeiro and in located Investors in the cities of São Paulo and of Rio de Janeiro.